(untitled) (Al-Academy, 2024)
This research aims to:1 – Make a proposed module for (aesthetics) for the second stage - Department of Art Education under education theories.2 - Verification from the effect of the proposed module on student achievement and motivation towards learning aesthetics material. To verification the second goal we wording these two hypotheses:1- There are no individual differences with statistically significant at level (0.05) between the student’s scores average. (Experimental group ) who studied according to the proposed module and the average student’s scores (control group) who studied in the usual way for the achievement test for the Aesthetics material.2- There are no individual differences with statistically significant at level (0.05) between the student’s scores average. (Experimental group) who studied according to the proposed module and the average student’s scores (control group) who studied in the usual way for the motivation measurement for the Aesthetics material.This research is limited to the following determinants.1 – The times temporal: first semester in the academic year 2011-20122 – The area temporal for second stage - Department of Art Education - college of Fine Arts in Baghdad3-The objectivity temporal: The proposed module for Aesthetics according to under the education theories .The second chapter includes two units, the first units (oriented cognitive science), and the second unit handled (relationship aesthetic experiences stereotypes units), and we can notes these two units in chapter two .Third chapter show the search procedures of (module design, make the achievement test, and design experience of the unit).The fourth chapter discussed the most important result after application module proposed (Experimental group.) according to plan teachingAnd the researcher supported his opinion with the most important conclusions of the results, and the Researcher gives some recommendations in light of the results and the conclusions of research, at the end of the chapter researcher suggested some useful suggestion for Subsequent study.